Math Problem Statement

make just the table and dont print any thing else just the table using T and F

Prove that p ∨ (¬p ∧ ¬q) ∨ (p ∧ q) = p ∨ (¬p ∧ ¬q)

Solution

Here's the truth table as requested:

pq¬p¬q¬p ∧ ¬qp ∧ qp ∨ (¬p ∧ ¬q)p ∨ (¬p ∧ ¬q) ∨ (p ∧ q)
TTFFFTTT
TFFTFFTT
FTTFFFFF
FFTTTFTT

If you have any questions or want more details, let me know!

Related Questions:

  1. How can we simplify expressions using Boolean algebra?
  2. What are the common laws used in logical expressions?
  3. What is the significance of a truth table in logical proofs?
  4. How do we construct a truth table for more complex expressions?
  5. Can we represent these logical expressions using Venn diagrams?

Tip: When building truth tables, ensure every possible combination of truth values for the variables is covered for accurate results.

Ask a new question for Free

By Image

Drop file here or Click Here to upload

Math Problem Analysis

Mathematical Concepts

Propositional Logic
Boolean Algebra

Formulas

p ∨ (¬p ∧ ¬q)
p ∧ q

Theorems

Distributive Laws
De Morgan's Law
Idempotent Law

Suitable Grade Level

Undergraduate (or Advanced High School)